54.5k views
8 votes
2x - x + 7 = x + 3 + 4

User Elachere
by
5.1k points

1 Answer

5 votes

Answer:0

Explanation:

Simplifying

2x + -1x + 7 = x + 3 + 4

Reorder the terms:

7 + 2x + -1x = x + 3 + 4

Combine like terms: 2x + -1x = 1x

7 + 1x = x + 3 + 4

Reorder the terms:

7 + 1x = 3 + 4 + x

Combine like terms: 3 + 4 = 7

7 + 1x = 7 + x

Add '-7' to each side of the equation.

7 + -7 + 1x = 7 + -7 + x

Combine like terms: 7 + -7 = 0

0 + 1x = 7 + -7 + x

1x = 7 + -7 + x

Combine like terms: 7 + -7 = 0

1x = 0 + x

1x = x

Solving

1x = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.

1x + -1x = x + -1x

Combine like terms: 1x + -1x = 0

0 = x + -1x

Combine like terms: x + -1x = 0

0 = 0

Simplifying

0 = 0

The solution to this equation could not be determined.

User RedDwarfian
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.